Teacher Candidates' Expectations: Equity Education, Critical Literacy, and Indigenous Students' Epistemologies - Lorenzo Cherubini (University of Windsor, 2020)
Culturally responsive teachers respond positively to students' cultural norms and traditions by creating inviting and meaningful learning opportunities that distinguish between Indigenous and western perspectives; however, in classrooms where teachers' understanding of Indigenous epistemologies and worldviews are not necessarily sufficiently represented, Indigenous students not only often feel marginalized and isolated but disengaged from Eurocentric curriculum and texts that fail to incorporate their histories and traditions. This study focuses on the expectations and perceptions of teacher candidates (prior to their field practicum experiences in classrooms) related specifically to equity education, reflective practice, and critical literacy. The mixed-methods study examines prospective teachers' perceptions of issues related to Indigenous students, and how public education policy and practice manifests in classrooms. The findings suggest that prospective teachers are doubtful of the fact that Indigenous voices are being presented competently to enhance student learning and foster Indigenous student identity. Moreover, prospective teachers anticipate a fundamental disconnect between the Ontario policy outcomes related to Indigenous education and the practice of teachers in school.